Correlation between serum uric acid level and blood pressure fluctuation in peritoneal dialysis patients - WANG Jie; CHU Rui; TIAN Na; CHEN Meng-hua (Linchuang shenzangbing zazhi)
Objective To investigate the correlation between serum uric acid level and blood pressure fluctuation in peritoneal dialysis patients. Methods This was a retrospective cohort study. Patients received stable maintenance ambulatory peritoneal dialysis from January 1 st,2008 to October 1 st,2016 in our peritoneal dialysis center. The patients’ demographic data,clinical laboratory indicators,and the blood pressure and uric acid status in baseline,at 3 rd,6 th,9 th and 12 th month after the dialysis were collected. The patients were divided into three groups according to the uric acid levels by the three division method. The clinical characteristics,blood pressure and blood fluctuation were compared among the groups. The correlation between uric acid levels and blood pressure fluctuation was analyzed by the correlation analysis and Logistic regression analysis. Results A total of 302 cases were enrolled in this study,including 157 males(52 %) with the average age of(50. 6 ± 13. 3) years and the median dialysis age of 41. 75 months(26. 35-67. 70). The mean uric acid level in all patients was(369. 49 ± 81. 96) μmol/L. The uric acid levels in M1,M2 and M3 groups were < 328,328-395,and > 395 μmol/L. M3 group had more males,higher BMI,higher serum phosphoru,serum creatinine,serum potassium,serum albumin and cholesterol levels than in M1 group(P < 0. 05 for all). The age and high density lipoprotein decreased with the increase of uric acid level in M3 group as compared with those in M1 group(P < 0. 05). The serum calcium,phosphorus and creatinine levels in M3 group were significantly higher than in M2 group(P < 0. 05). Baseline systolic blood pressure and diastolic blood pressure increased with the increase of uric acid levels in the three groups(P < 0. 01). Compared with the other two groups,The systolic and diastolic blood pressure in M3 group fluctuated more than that in M1 and M2 groups(P< 0. 05). The regression analysis suggested that there was a significantly linear positive correlation between systolic blood pressure fluctuation and diastolic blood pressure fluctuation with baseline uric acid(r = 0. 17,P = 0. 002; r = 0. 13,P = 0. 03). Multivariate Logistic regression analysis showed that elevated baseline uric acid was an independent risk factor for high systolic blood pressure fluctuation in peritoneal dialysis patients(OR = 1. 05,95 % CI 1. 02-1. 09,P < 0. 05). Conclusions In maintenance peritoneal dialysis patients,uric acid level is positively correlated with blood pressure fluctuation. The baseline uric acid elevation is an independent risk factor for hypertension and blood pressure fluctuation. Controlling the level of uric acid may be helpful to the control of hypertension.